Registration of 'Prevail' Hard Red Spring Wheat. Issue 1 (6th October 2016) - Glover, K. D.; Kleinjan, J. L.; Jin, Y.; Osborne, L. E.; Ingemansen, J. A.; Turnipseed, E. B.; Ohm, J. B.
Abstract : Grower and end‐user acceptance of new hard red spring wheat (HRSW; Triticum aestivum L.) cultivars largely depends on satisfactory agronomic performance, end‐use quality potential, and disease resistance levels. Additional characteristics, such as desirable plant height, can also contribute to grower acceptance. The objective of this research was to release a short‐statured HRSW cultivar with competitive grain yield and acceptable levels of end‐use quality characteristics and Fusarium head blight (FHB) resistance. 'Prevail' (Reg. No. CV‐1121; PI 672486) HRSW was developed at South Dakota State University (SDSU) and released by the South Dakota Agricultural Experiment Station (SDAES) in early 2014. The cross SD3720/MN98389‐A was completed during fall 2002, and the resulting population was advanced via an early‐generation bulk‐testing program where F6:8 seed was included in the 2008 preliminary yield trial and the line was designated as SD4178. SD4178 also was tested in the advanced yield trial from 2009 through 2013. Prevail was released primarily for its combination of high yield potential and desirable plant height that is significantly shorter than most other HRSW cultivars developed by the SDSU‐HRSW breeding program.